KOMPLEKSITAS PSIKOLOGIS TOKOH-TOKOH NOVEL SEDARA CINTA KARYA HERMES DIONE - Rahayu, Monica Febrianti (Humanis, 2013)
This article analyzed novel Sedara Love, by Hermes Dione. This novel illustrates complexicity,betrayal, choice. The theories which are applied in this analysis are structuralism theory by Teeuw and psychological personality theory by Sigmund Freud.This novel firstly analyzes the relation of the structure of characterization, plot, and setting. Second, it analyzes the psychologyfigures of novel SedaraCinta. The reason in two theories applied : structural theory and psycology theory. Choosing this data to be analyzed is because the interesting plot dan give moral value for the readers for faithful with couple. This novel is choosen to be analyzed because it complexityof figures, and the response of figures of SedaraCinta novel in facing problem and the response of two figures to shake off the problem.
Keywords: structuralism, psycology, andcomplexicity